1979
DOI: 10.3758/bf03335015
|View full text |Cite
|
Sign up to set email alerts
|

3-Hz brain stimulation interferes with various aspects of the kindling effect

Abstract: These exploratory experiments investigated the effect of 3·Hz brain stimulation on behavior induced by 60·Hz brain stimulation when the former was presented simultaneously with, or following, the latter. In the simultaneous case, 3-Hz stimulation to one amygdala and 60 Hz to the other produced a slower kindling rate than did bilateral stimulation with 60 Hz. When 3-Hz stimulation followed six convulsion trials of 60-Hz stimulation, there was no effect on the convulsive tendency; however, with rats in which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The brain coordinates for electrode implantation were the same as in many experiments in our laboratory: .5 mm posterior to bregma, 4.5 mm from midline, 8.5 mm from skull (bregma as reference point; Gaito, 1979). With these coordinates, the electrode tips were aimed at the central part of the amygdala, approximately in the intercalated nucleus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The brain coordinates for electrode implantation were the same as in many experiments in our laboratory: .5 mm posterior to bregma, 4.5 mm from midline, 8.5 mm from skull (bregma as reference point; Gaito, 1979). With these coordinates, the electrode tips were aimed at the central part of the amygdala, approximately in the intercalated nucleus.…”
Section: Methodsmentioning
confidence: 99%
“…In a series of experiments, we found that 1-or 3-Hz sine-wave stimulation at moderate intensities before and/or after a 6O-Hzstimulation trial suppressed the tendency of the 60-Hz current to produce kindling behavior (Gaito, 1979, 1980a, 1980bGaito, Nobrega, & Gaito, 1980). The experiments with 3-Hz stimulation were conducted at an intertrial interval of 1 h between the imposition of the 3-and 6O-Hz stimulation trials.…”
mentioning
confidence: 99%